Supramolecular association in the triclinic (Z′ = 1) and monoclinic (Z′ = 4) polymorphs of 4-(4-acetylphenyl)piperazin-1-ium 2-amino4-nitrobenzoate - Jotani, Mukesh M.; Wardell, James L.; Tiekink, Edward R. T. * (De Gruyter for Oldenbourgh Verlag, 2019)
Crystallography reveals two polymorphs for the salt [4-(4- acetylphenyl)piperazin-1-ium][2-amino-4-nitrobenzoate], a monoclinic form (2; modelled as P21/n with Z' = 4) formed directly from the reaction mixture, and a triclinic form (1; Z' = 1) isolated from recrystallisation. Relatively minor differences are noted in the conformations of the anions and of the cations, mainly relating to the twist of, respectively, the carboxylate groups and piperazin-1-ium rings with respect to the phenyl rings they are connected to. The key feature of the packing of both forms is the formation of charge-assisted ammonium-N‒H…O(carboxylate) hydrogen bonds which lead to cyclic 12-membered {...HNH...OCO}2 synthons in the case of 1 but, supramolecular chains in 2. The three-dimensional architecture in the crystal of 1 is further stabilised by amine-N‒H…O(nitro) and amine-N‒H…O(acetyl) hydrogen bonds, leading to double-layers in the bc-plane, which are linked along the a-axis by methylene-C10‒H…O(carboxylate) and -stacking interactions. The combination of ammonium-N‒H…O(carboxylate) and amine-N‒H…O(carboxylate, acetyl) hydrogen bonds consolidate the three-dimensional packing in the crystal of 2. The greater crystal density, packing efficiency and calculated lattice energy for 1 compared with 2, suggest the former to be the thermodynamically most stable crystal. An analysis of the Hirshfeld surfaces for 1 and 2 reveal distinctive features that differentiate between the constituents of the two forms and between the ions comprising the asymmetric unit of 2.